Attachment style predicts affect, cognitive appraisals, and social functioning in daily life - Sheinbaum, Tamara; Kwapil, Thomas R.; Ballespí, Sergi; Mitjavila, Mercè; Chun, Charlotte A.; Silvia, Paul J.; Barrantes-Vidal, Neus (Frontiers in Psychology, 2015)
The way in which attachment styles are expressed in the moment as individuals navigate their real-life settings has remained an area largely untapped by attachment research. The present study examined how adult attachment styles are expressed in daily life using Experience Sampling Methodology (ESM) in a sample of 206 Spanish young adults. Participants were administered the Attachment Style Interview and received personal digital assistants that signaled them randomly eight times per day for one week to complete questionnaires about their current experiences and social context. As hypothesized, participants’ momentary affective states, cognitive appraisals, and social functioning varied in meaningful ways as a function of their attachment style. Individuals with an anxious attachment, as compared with securely attached individuals, endorsed experiences that were congruent with hyperactivating tendencies, such as higher negative affect, stress, and perceived social rejection. By contrast, individuals with an avoidant attachment, relative to individuals with a secure attachment, endorsed experiences that were consistent with deactivating tendencies, such as decreased positive states and a decreased desire to be with others when alone. Furthermore, the expression of attachment styles in social contexts was shown to be dependent upon the subjective appraisal of the closeness of social contacts, and not merely upon the presence of social interactions. The findings support the ecological validity of the Attachment Style Interview and the person-by-situation character of attachment theory. Moreover, they highlight the utility of ESM for investigating how the predictions derived from attachment theory play out in the natural flow of real life.